Instrumented Impact Testing 1974
DOI: 10.1520/stp32192s
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Impact Testing of Titanium Alloys

Abstract: The dynamic fracture toughness was determined for two titanium alloys (Ti-6A1-4V and Ti-6A1-6V-2Sn) from different suppliers and in various heat-treated conditions. The strain-rate effect associated with the dynamic test is shown to increase the fracture toughness for all the alloys with the exception of mill-annealed and duplex-annealed Ti-6A1-6V-2Sn, where the fracture toughness was found to be independent of strain rate. Dial energy per unit specimen area (W/A)d for precracked Charpy specimens can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This equation is available where the load is seen to increase linearly until maximum load is reached where fracture is initiated. K Id-Energy calculated by Ronald's energy equation [5]. ---------------------------------------- -----------------------------------------CT : Al7175-T74(dynamicc:strain) CT : Al7175-T74(dynamic:ASTM) Venkatanarayana [6] reported that the strength properties of M250 are independent of strain rate.…”
Section: Resultsmentioning
confidence: 99%
“…This equation is available where the load is seen to increase linearly until maximum load is reached where fracture is initiated. K Id-Energy calculated by Ronald's energy equation [5]. ---------------------------------------- -----------------------------------------CT : Al7175-T74(dynamicc:strain) CT : Al7175-T74(dynamic:ASTM) Venkatanarayana [6] reported that the strength properties of M250 are independent of strain rate.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore , if any correlation is expected , it should be between dynamic fracture toughness , K Id, and impact W/A . In studies on the titanium alloys , K Id calculated from the instrumented precracked C y load values were higher than the measured valid K Ic values and tended to produce a reasonable correlation with impact W/A values (Ewing and Raymond , 1974).…”
mentioning
confidence: 76%
“…Data on Ti-6-4 (Ewing and Raymond , 1974) include d three combinations of heat s and specimen orientations , all for the mill annealed condition . The…”
mentioning
confidence: 99%